What paediatricians need to know about modern urologic management of vesicoureteral reflux - Goulin, Jeanne; Demède, Delphine; Ranchin, Bruno; Mosca, Mélodie; De-Mul, Aurélie; Bidault Jourdainne, Valeska (Frontiers in Pediatrics, 2025)
Vesicoureteral reflux (VUR) is a common urological disorder in children, and its prevalence is difficult to determine, as many VUR cases remain asymptomatic. VUR is considered nearly physiological during infancy and often resolves spontaneously within the first few years of life. Most patients present with low-grade VUR, which is thought to be caused by an insufficient intramural course of the ureter in the bladder wall, a condition that tends to improve as the child grows and develops. The higher the grade of VUR , the lower the probability of spontaneous resolution of this condition during early childhood. Knowledge of the pathophysiology of VUR and renal scarring has evolved over the past decades. While surgical correction of VUR is thus often discussed, it is ultimately reserved for very selected cases, mainly when high-grade VUR persists despite the correction of voiding disorders in toilet-trained children and is associated with recurrent febrile UTI. European and other international pediatric urology societies have published guidelines for VUR management in children. With minimally invasive surgery becoming increasingly common among pediatric urologists, treatment modalities for VUR have evolved significantly, and endoscopic, laparoscopic, and robotic-assisted procedures now play a central role in surgical management. The recently updated ESPU/EAU guidelines are considered as a reference for pediatric urologists across Europe. In this review, we examine the recent literature and these guidelines to provide pediatricians with up-to-date data on VUR pathophysiology, its renal consequences, and current approaches to urological management.